Safety climate and accidents at work: Cross-sectional study among 15, 000 workers of the general working population. (January 2017) - Ajslev, Jeppe; Dastjerdi, Efat Lali; Dyreborg, Johnny; Kines, Pete; Jeschke, Katharina Christiane; Sundstrup, Emil; Jakobsen, Markus Due; Fallentin, Nils; Andersen, Lars Louis
Highlights: Risk for accidents as a function of an increasing number of safety climate problems is investigated. A five-item short version of the NOSAQ-50 questionnaire is validated. Younger workers are more likely to experience safety climate problems and accidents. Transport, construction, manufacturing and service workers report more safety climate problems. Abstract: Aim: Occupational safety climate is utilized as a way to measure the risk of accidents and injuries at work. This study investigates which factors are associated with safety climate and accidents at work. Methods: In the 2012 round of the Danish Work Environment and Health Study, 15, 144 workers from the general working population of Denmark replied to questions about safety climate and accidents at work. Mutually adjusted logistic regression analyses determined the association between variables. Results: Within the last year, 5.7% had experienced an accident resulting in sickness absence. The number of safety climate problems was progressively associated with the odds ratio (OR) for accidents. For one safety climate problem the OR for accidents was 2.01 (95% CI 1.67–2.42), for four or more safety climate problems the OR was 4.57 (95% CI 3.64–5.74). Young workers (18–24 years) had higher odds of accidents (OR 1.36 [95% CI 1.02–1.81]). Using safety climate as outcome and excluding those who previously experienced an accident, the OR for experiencing safety climate problems was 1.98 (95% 1.66–2.36) among young workers. Using office and educational work as reference, transport or alone work, construction work, manufacturing work, and service and kitchen work had highest odds for experiencing safety climate problems. Conclusion: A higher number of safety climate problems are progressively associated with increased odds for experiencing accidents. Young workers are more likely to experience safety climate problems and accidents at work. Especially transport, construction, manufacturing and service workers are more likely to experience safety climate problems.